Implementasi Frontend Sistem Pelaporan Tugas Harian Berbasis Web dengan Pendekatan Gamifikasi Menggunakan Vue.js - Riza Al Hambra; Novi Tristanti (Bulletin of Computer Science Research, 2026)
The phenomenon of students' lack of discipline in completing and reporting daily tasks is an academic problem that impacts learning achievement. Monotonous manual reporting systems often reduce intrinsic motivation and student participation rates. This study aims to design and implement a web-based daily task reporting system frontend with a gamification approach using the Vue.js framework, and analyze its impact on improving discipline. The research location is at Universitas Muhammadiyah Karanganyar involving 10 active students as trial respondents. The research method used is a qualitative approach with an implementative case study type. The system interface was developed using Vue.js 3, Pinia as state management, and Vue Router. Data collection techniques included participatory observation, in-depth interviews, and User Acceptance Test (UAT) questionnaires with a 1 to 5 Likert scale. Data testing was analyzed using the Miles and Huberman model consisting of data reduction, data display, and drawing conclusions. Interim research results show the functional success rate of the frontend reached 88 percent in the localhost environment. The UAT questionnaire obtained an overall average score of 4.21 which is classified as very good. Gamification features became the most preferred element by 60 percent of respondents, which effectively encouraged students' disciplined behavior in submitting assignments on time.